IMPLEMENTASI PROGRAM CVC (CUSTOMS VISIT CUSTOMER) KANTOR PENGAWASAN DAN PELAYANAN BEA CUKAI TIPE MADYA PABEAN B DUMAI - Heriadi "; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Office and Customs Service Type B Dumai present provide assistance to remove service users from the current conditions through the CVC Program (Customs Visit Customer). This study aims to determine the stages of Program Implementation CVC and to determine the impact of the implementation of CVC Program to service users as a recipient.This research uses qualitative methods by using Lasswell Model. The subjects consisted of five informants selected through purposive technique. Data collection is done through observation, interview and documentation. Data analysis using huberman interactive model. And to achieve the validity of data in this study, the authors use the method of extension of participation and triangulation.The results of this study indicate that CIS (Counseling and Information Services), which acts as public relations KPPBC TMP B Dumai perform several stages in implementing CVC program (Customs Visit Customer) such as: First is preceded by the selection of service users. The selection is in the form of data and information that will be processed. Second, communication with service users, at this stage public relations PR is demanded to communicate information to service users about the implementation of CVC Program. Third, , administration. At this stage make the administration in writing in the form of a letter that contains information. Fourth, introduction of the institution, at this stage public relations or concerned from both sides should introduce themselves to represent from their intansi. Fifth, delivery and problem solving, at this stage the occurrence of good lead communication (feedback) which where the representative intansi convey the problem and directly solved by the relevant sections. Sixth, handover of the eye cendra, symbolizes the communication symbol. To see the impact received by service users on the implementation of CVC program seen from two aspects namely Performance and Economic (People and Profit).Keywords: Implementasi, Program, Customes